Emotion Regulation Protects Against Recurrence of Depressive Symptoms Following Inpatient Care for Major Depressive Disorder. Issue 6 (November 2017) - Ebert, David D.; Hopfinger, Lisa; Bockting, Claudi L.H.; Berking, Matthias
Abstract: Relapse following response in psychotherapy for major depressive disorder (MDD) is a major concern. Emotion regulation (ER) has been discussed as a putative emerging and maintaining factor for depression. The purpose of the present study was to examine whether ER protects against recurrence of depression over and above residual symptoms of depression following inpatient care for MDD. ER skills (ERSQ-ES) and depression (HEALTH-49) were assessed in 193 patients with MDD (age, M = 47.4, SD = 9.6, 75.1% female, 100% Caucasian) at treatment discontinuation, 3 and 12 months after treatment. Multiple hierarchical regressions were used to examine general and specific ER as predictors of depressive symptoms at follow-ups. Higher general ER predicted lower depression over and beyond residual symptoms of depression at 3-month follow-up among treatment responders but not among treatment nonresponders. With regard to specific ER skills, readiness to confront and a cceptance of undesired emotions predicted lower depressive symptoms beyond residual symptoms of depression 12 months, respectively 3 and 12 months after treatment. Findings of the present study indicate that targeting general ER might be more important for remitted and less important for nonremitted patients. Enhancing ER should hence be realized in a sequential treatment design, in which a continuation phase treatment with a specific focus on ER directly follows, once patients sufficiently responded to treatment. Acceptance of undesired emotion and readiness to confront situations that cue these emotions appear to be particularly important for protecting against recurrence of depression. Future research should clarify whether findings can be generalized to outpatient care. Highlights: General ER did predict depressive symptoms after CBT in treatment responders and not in treatment nonresponders. Acceptance and readiness to confront predicted depressive symptoms both in treatment responders and nonresponders. This finding holds true even with controlling for residual depressive symptoms as one of the most important predictors for relapse. Implementing ER in the treatment of depression may help to maintain long-term CBT success. Results suggest that targeting ER should be realized in a sequential treatment design, once treatment response has been achieved, e.g., in a continuation phase treatment.